Automatización del proceso de fabricación de microfilamentos de policaprolactona - Cordero-Umaña, Bernal Alejandro (Instituto Tecnológico de Costa Rica, 2018)
The Mechanics of Materials Laboratory of the Costa Rican Institute of Technology School of Science and Materials Engineering dedicates itself to the research, development and innovative application of new compounds and materials. The project developed in this paper derives itself from an on-course investigation titled “Development of an In-Vitro Study System adaptable to a Dynamic Test equipment”. It is intended, in such project, to subject different specimens made of polycaprolactone (PCL) to several mechanic tests to stimulate cellular growth. The afore mentioned specimens can be scaffolds whose purpose is to mimic human bone structure or they can also be microfilaments that resemble the thickness and shape of skeleton muscle fibers. In this document, a solution to an existing problem in the process of fabrication of PCL microfilaments is designed. At present moment, this is a manual process that presents several deficiencies such as, manual stretching of the filament. This leads to resulting threads that are unfit to be used as cellular inoculation scaffolds due to unmet dimensional characteristics requirements. As a solution proposal to the afore stated problem, an automatic stretching system was designed. Such system includes a material recollection spool and two rollers in a tire traction system configuration. The latter are coupled to a speed-controlled DC motor to ensure that the tension to which the material is subjected is always constant. Given the mechanical properties of PCL, it is known that once the material surpasses its yield strength, it will elongate at a rate in which its thickness will be reduced at a constant rate as well, as long as the material’s ultimate strength is not exceeded. This easy to use automatic system yields a better and more efficient harness of the raw material at disposal.

El Laboratorio de Mecánica de Materiales de la Escuela de Ciencia e Ingeniería de los Materiales del ITCR se dedica a la investigación y desarrollo de nuevos compuestos y aplicaciones novedosas de estos. El proyecto que se desarrolla en este documento se deriva de una investigación en curso titulada “Desarrollo de un Sistema de Estudios In-Vitro adaptable en equipo de Pruebas Dinámicas”. En dicha investigación se pretende someter a diversas pruebas mecánicas probetas hechas de policaprolactona (PCL) para estimular el crecimiento celular en ellas. Dichas probetas pueden ser andamios que simulan la estructura ósea humana o pueden ser microfilamentos que asemejen el grosor de fibras de músculo esquelético. En este documento se desarrolla una solución a un problema presente en el proceso de fabricación de microfilamentos de PCL. Actualmente es un proceso manual que presenta varias deficiencias como, por ejemplo, estirado manual del filamento. Esto resulta en hilos que no presentan las características dimensionales necesarias para que puedan utilizarse como probeta para la inoculación celular. Como propuesta a solución se diseñó un sistema automático que consta de un carrete de recolección de material y dos rodillos en configuración de sistema de arrastre tipo llanta. Estos últimos se acoplan a un motor CD con control de velocidad de modo que se asegura que la tracción a la cual se somete el material extruido es constante. Dadas las propiedades mecánicas del PCL se sabe que una vez que el material sobrepasa su esfuerzo de fluencia, este se elongará reduciendo su diámetro de manera constante, siempre y cuando no se supere el esfuerzo último a tensión. Este es un sistema que es fácil de operar y cuya implementación se traduce en un mejor aprovechamiento de la materia prima que se dispone.
Informe de proyecto de graduación (Licenciatura en Ingeniería Mecatrónica) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Mecatrónica, 2018.
Keywords: Guías mecánicas; Ensamblado automático; Inoculación; Propiedades mecánicas; Sistema de control; Research Subject Categories::TECHNOLOGY::Engineering mechanics; Control system; Mechanical properties